Subtitling Strategies and Acceptability of Verbal Humor in Superstore Seasons 5 and 6 (2019-2021) - Venezia, Cherlie; Fatimah, Rezki (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2025)
In this study, the researchers focus on the types of humor based on the theory of Raphaelson-West (1989), translation strategies according to Gottlieb (1992), and the level of translation acceptability according to Nababan (2012) by using qualitative descriptive method which is used because the purpose of this study is to explain the phenomenon of translating humor subtitles in the Superstore series. The results show that the most common type of humor is universal humor with a total of 48 data, cultural humor with 37 data and linguistic humor with 25 data. The most frequently used translation strategy in the subtitles is transfer strategy with 43 data, while expansion and resignation are the least used with 2 data. Of the 110 data analyzed, 67 data fall into the acceptable category and only 3 data are unacceptable, which means that the subtitle translation is acceptable. Data collection is done by watching all seasons then selecting utterances that contain humor and classifying them based on the theory used. The transfer strategy is most used for universal humor, while paraphrasing is more dominant in cultural humor. Thus, the translation of verbal humor in the series is natural and relevant to the Indonesian language, and is able to maintain meaning and humor.